2023
DOI: 10.3389/fpsyg.2023.1101520
|View full text |Cite
|
Sign up to set email alerts
|

(Mis-)use of standard Autopilot and Full Self-Driving (FSD) Beta: Results from interviews with users of Tesla's FSD Beta

Abstract: Tesla's Full Self-Driving Beta (FSD) program introduces technology that extends the operational design domain of standard Autopilot from highways to urban roads. This research conducted 103 in-depth semi-structured interviews with users of Tesla's FSD Beta and standard Autopilot to evaluate the impact on user behavior and perception. It was found that drivers became complacent over time with Autopilot engaged, failing to monitor the system, and engaging in safety-critical behaviors, such as hands-free driving,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 58 publications
2
12
0
Order By: Relevance
“…Undertrust and disuse can diminish the projected benefits of higher automation levels. In our recent interview study with 103 users of Tesla’s Autopilot and Full-Self-Driving (FSD) Beta system, overtrust in Level 2 capability was associated with eyes-off, mind-off and fatigued driving (e.g., drivers actively manipulating the steering wheel, and falling asleep behind the steering wheel with Autopilot engaged) ( Nordhoff et al, 2023 ). Disuse refers to not using automation when it would, in fact, be beneficial ( Lee, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Undertrust and disuse can diminish the projected benefits of higher automation levels. In our recent interview study with 103 users of Tesla’s Autopilot and Full-Self-Driving (FSD) Beta system, overtrust in Level 2 capability was associated with eyes-off, mind-off and fatigued driving (e.g., drivers actively manipulating the steering wheel, and falling asleep behind the steering wheel with Autopilot engaged) ( Nordhoff et al, 2023 ). Disuse refers to not using automation when it would, in fact, be beneficial ( Lee, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…The patient in this study, like normally sighted drivers who used partially and conditionally automated driving systems in prior studies, 3–5 reported an increased frequency of long-distance trips after using Tesla Autopilot and changes in route choice after using the FSD Beta system. Drivers, in general, are more willing to engage in leisure driving activities and fulfill unmet travel needs owing to the ease of travel provided by the automated system and to gain experience and explore the system's usefulness 3,5 . Furthermore, drivers with vision impairments can now drive in situations previously inaccessible to them, leading to increased driving exposure alongside normally sighted drivers.…”
Section: Discussionmentioning
confidence: 51%
“…Drivers, in general, are more willing to engage in Identifies stop signs and traffic lights and automatically slows the car to a stop on approach to a red light or stop sign, with the active supervision of the driver Autosteer on City Streets (Beta) leisure driving activities and fulfill unmet travel needs owing to the ease of travel provided by the automated system and to gain experience and explore the system's usefulness. 3,5 Furthermore, drivers with vision impairments can now drive in situations previously inaccessible to them, leading to increased driving exposure alongside normally sighted drivers. However, extended travel time in more diverse driving situations with the system may lead to new safety risks for drivers with vision impairments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations